2013
DOI: 10.1097/01.prs.0000434415.70711.49
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Breasts and Psychosocial, Sexual, and Physical Well-Being after Breast Augmentation in Male-to-Female Transsexuals

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 13 publications
7
68
3
Order By: Relevance
“…Most studies point out the substantial risks of these surgeries (Horbach et al, 2015), whereas data collection via surveys obtained similarly high self-reported complication rates (Lawrence, 2006). The high number of satisfied respondents found in the present study is comparable to earlier studies (Bouman et al, 2016;Buncamper et al, 2015;De Cuypere et al, 2005;Horbach et al, 2015;Lawrence, 2003;Lawrence, 2006;Nelson, Whallett, & McGregor, 2009;Rehman et al, 1999;Smith et al, 2005;Weigert et al, 2013) and emphasizes the effectiveness of gender-affirming procedures. Yet, most treatment evaluation studies have collected data in a clinical setting, whereas the present study reports on a cohort that was surveyed in their home environment with limited dependence on clinicians (although the participants were invited through the clinics).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Most studies point out the substantial risks of these surgeries (Horbach et al, 2015), whereas data collection via surveys obtained similarly high self-reported complication rates (Lawrence, 2006). The high number of satisfied respondents found in the present study is comparable to earlier studies (Bouman et al, 2016;Buncamper et al, 2015;De Cuypere et al, 2005;Horbach et al, 2015;Lawrence, 2003;Lawrence, 2006;Nelson, Whallett, & McGregor, 2009;Rehman et al, 1999;Smith et al, 2005;Weigert et al, 2013) and emphasizes the effectiveness of gender-affirming procedures. Yet, most treatment evaluation studies have collected data in a clinical setting, whereas the present study reports on a cohort that was surveyed in their home environment with limited dependence on clinicians (although the participants were invited through the clinics).…”
Section: Discussionsupporting
confidence: 81%
“…Minor regret is considered as disappointment and can overlap with dissatisfaction. In general, the literature gives high percentages of satisfaction with GAS procedures: breast augmentation 87% to 100% (De Cuypere et al, 2005;Smith, van Goozen, Kuiper, & Cohen-Kettenis, 2005;Weigert, Frison, Sessiecq, Al Mutairi, & Casoli, 2013), vaginoplasty 83% to 100% (De Cuypere et al, 2005;Horbach et al, 2015;Lawrence, 2003;Rehman, Lazer, Benet, Schaefer, & Melman, 1999;Smith et al, 2005), subcutaneous mastectomy 92% to 100% (De Cuypere et al, 2005;Nelson, Whallett, & McGregor, 2009;Smith et al, 2005), and phalloplasty 100% (De Cuypere et al, 2005). Clinical evaluation studies show positive appraisal of both genital functionality and aesthetics after surgery, whereas sexual outcomes were found to be less positive (Bouman et al, 2016;Buncamper et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a surgeon with full understanding of male chest tissue characters and a transwomen with full knowledge of large volume implant complications shall pave way for an esthetically lasting prosthetic augmentation mammoplasty. 6 Transgender persons seek surgical interventions such as PAM to achieve the physical transformations that hormone therapy alone cannot produce. [7][8][9][10][11][12] Author's protocol of minimum 2-year preoperative hormonal therapy results in mild-to-moderate breast growth in transwomen facilitating PAM with good stretchable envelope and well developed nipple and areola that culminates in good esthetic results.…”
Section: Discussionmentioning
confidence: 99%
“…Genital surgeries are also sometimes performed earlier outside of the recommendations on a case‐by‐case basis 27,28 . Importantly, surgeries for transgender individuals are medically necessary procedures, proven to improve dysphoria, mental health, and quality of life, 26,29‐33 and should not be viewed as elective 14,15 …”
Section: Transitioningmentioning
confidence: 99%